Optimalisasi Pemerintah Desa Karangwuni Polokarto Sukoharjo Dalam Menjadikan Es Gempol Pleret Sebagai Warisan Budaya Tak Benda (Perspektif Hukum Pemerintahan Desa) - Muhamad Nandafa Putra Rahman (Jurnal Ilmu Hukum, Humaniora dan Politik, 2025)
Es Gempol Pleret is a traditional culinary specialty of Karangwuni Village which is now facing the threat of extinction due to changes in lifestyle and the lack of interest of the younger generation. This study aims to analyze the role of the Karangwuni Village Government in making Es Gempol Pleret an Intangible Cultural Heritage (ICH) through a descriptive qualitative method with observation, interview, and document study techniques. The results show that the village government has made various efforts such as promotion, branding, and organizing cultural events, but still faces challenges in the form of limited regulations, human resources, and the absence of official recognition as ICH. To preserve it, synergy is needed between the government, community, and stakeholders through village regulations, education for the younger generation, marketing strategies, and legalization at the provincial or national level.